IMPACT OF THE INSERTION OF THE USE OF HOSPITAL PIJAMAS AS A STANDARD OPERATING PROCEDURE IN THE SUPERVISED STAGE OF THE PHYSIOTHERAPY COURSE: EXPERIENCE REPORT (CIPEEX, 2022)
TO REPORT THE EXPERIENCE OF THE TEACHERS OF THE PHYSIOTHERAPY COURSE TOGETHER WITH THE STUDENTS WHO ARE MEMBERS OF THE ACADEMIC DIRECTORY OF PHYSIOTHERAPY (ADF) IN THE PROCESS OF IMPLEMENTING THE USE OF HOSPITAL PAJAMAS TO REPLACE THE WHITE COAT IN THE INTERNSHIP, IN THE YEAR 2022. A REQUEST WAS MADE BY THE STUDENTS OF THE PHYSIOTHERAPY COURSE OF A PRIVATE UNIVERSITY VIA ADF, REQUESTING AUTHORIZATION TO USE GREEN HOSPITAL PAJAMAS, REPLACING THE STANDARD USE OF WHITE CLOTHING IN AN INTERNSHIP ENVIRONMENT, AIMING AT A BETTER RELATIONSHIP BETWEEN THE PHYSICAL THERAPIST AND THE PATIENT, REDUCING THE SYMPTOMS PRESENT IN THE SYNDROME. OF THE WHITE COAT, THE REDUCTION OF THE RISK OF CONTAMINATION IN THE WORK FIELDS, REDUCTION OF EXPENSES WITH MAINTENANCE OF THE WHITE CLOTHES. ALL INSTITUTIONAL PROCEDURES WERE CARRIED OUT, WHICH ARE: APPROVAL OF THE COLLEGIATE AND INTERNSHIP SUPERVISORS WITH UNANIMOUS MANIFESTATION, FOLLOWED BY EVALUATION BY THE ACADEMIC DEAN'S OFFICE. FOR APPROVAL, A SPECIFIC REGULATION WAS CARRIED OUT WITH A ROBUST THEORETICAL FRAMEWORK, GUIDANCE ON MAKING, ATTIRE, UNDRESSING, MAINTENANCE, HYGIENE, AND MANDATORY PLACES FOR THE USE OF CLOTHING, AFTER CARRYING OUT THE DOCUMENTATION, ACADEMIC DEAN'S OFFICE WAS IN FAVOR OF THE USE OF HOSPITAL PAJAMAS DURING THE SUPERVISED INTERNSHIP OF THE PHYSIOTHERAPY COURSE. IT IS POSSIBLE TO SUGGEST THAT THE COORDINATION OF THE COURSE TOGETHER WITH ACADEMIC DEAN'S OFFICE IS FAVORABLE TO BENEFICIAL CHANGES FOR THE WELL-BEING OF THE STUDENT. CURRENTLY, ITS INFLUENCE IS PERCEPTIBLE FOR PATIENTS WHO PRESENT THE WHITE COAT SYNDROME, THE INTERNS DEVELOP THEIR CARE WITH MORE COMFORT-MOBILITY, BEFORE THIS IT WAS A CHANGE THAT PROVIDES CONTINUITY TO THE EXCELLENCE STANDARD OF CARE PROVIDED DURING THE INTERNSHIP.
Keywords: Physiotherapy Course; Hospital Pajamas; University